The impact of earthquake anxiety on quality of life: the case of Türkiye - Capar, Hasim; Yelboga, Nurullah (BMC, 2025)
IntroductionSince the earthquakes cause many problems in psycho-socio-economic terms and deeply affect people's lives in different dimensions, they also negatively affect people's quality of life.ObjectiveThis study aims to reveal the earthquake anxiety of the Turkish people after the earthquake that occurred on February 6, 2023 and to examine the effects of this anxiety on the quality of life.MethodsThis cross-sectional study was conducted using an online survey method with 983 participants in seven regions of T & uuml;rkiye between March 10 and June 10, 2023. A sufficiently heterogeneous data was collected thanks to the representatives responsible for collecting data from different regions of T & uuml;rkiye. Both cluster and purposive sampling methods were used. It is possible that this may contain some biases. However, some steps were taken to get rid of these biases as much as possible. The study was conducted with the STROBE guide. Multiple linear regression analysis was performed.ResultsA very high and statistically significant negative correlation was found between earthquake anxiety and limitations due to emotional problems, emotional well-being, energy exhaustion and general health. The high level of earthquake anxiety of the participants decreases the score of being restricted due to emotional problems, emotional well-being, energy exhaustion, and the general health score which are parameters of quality of life. It should be noted that these results are reported under some limitations due to the sampling methodology and data collection method of the study. Accordingly, the results should be evaluated carefully in practice.ConclusionThe findings show that earthquake victims should be supported by providing psychological support and counseling through long-term mental health care policies.
Keywords: Anxiety; Earthquakes; Health; Life quality; Quality of life